EFFECT OF INITIAL IMPERFECTION ON ULTIMATE STRENGTH OF STIFFENED PANELS UNDER LONGITUDINAL COMPRESSION - Ling Lim, Hui (IRC, 2015)
The stiffened steel panel will experienced high stress when the deck and bottom shell of ship hulls experience bending compressive stress due to hogging and sagging bending moment. Failure of stiffened panel will also will lead to failure of ship hull girder. Therefore, stiffened steel panel has significant contribution to ship’s hull girder strength and stability. This paper is to analyse the effect of initial imperfection on the ultimate strength performance of the stiffened steel plate subjected to longitudinal compression. Initial imperfection may be present due to fabrication and manufacturing process of stiffened plate. It is evident that these initial imperfections lead to degradation of the load carrying capacity of the plate (Gandhi et al., 2012). Each level of initial imperfection for different type of plate slenderness is develop with empirical ULS formulae. The results are used to study the relationship between the ultimate strength of the stiffened plate, with various types of initial imperfection models under purely longitudinal compression action. The effect of initial imperfection is significant for column slenderness ratio less than 1.5. The empirical formula generated can be useful for ship manufacture in determine the ultimate strength stiffened panel. User can use the empirical formula to determine ultimate strength of their stiffened panel.